Why Is 10 Past 10 the Default Setting for Clocks and Watches in Advertisements? A Psychological Experiment - Karim, Ahmed A.; Lützenkirchen, Britta; Khedr, Eman; Khalil, Radwa (Frontiers in Psychology, 2017)
Have you ever noticed that in watch advertisements the time is usually set at 10:10? The reasons and psychological effects of this default time setting are elusive. In Experiment 1, we hypothesized that watches showing a time setting resembling a smiling face (10:10) would enhance emotional valence and intention to buy compared to a neutral time setting (11:30), whereas a time setting resembling a sad face (8:20) would have the opposite effect. Moreover, we investigated a possible interaction effect with the gender of the participants. In Experiment 2, we directly tested the hypotheses that watches set at 10:10 resemble a smiling face, whereas watches set at 8:20 resemble a sad face. The data of the first experiment reveal that watches set at 10:10 showed a significant positive effect on the emotion of the observer and the intention to buy. However, watches set at 8:20 did not show any effect on the emotion or the intention to buy. Moreover, watches set at 10:10 induced in women significantly stronger ratings of pleasure than in men. The data of the second experiment show that participants consistently perceive high resemblance between watches set at 10:10 and a smiling face as well as high resemblance between watches set at 8:20 and a sad face. This study provides for the first time empirical evidence for the notion that using watches with a time setting resembling a smiling face (like 10:10) can positively affect the emotional response of the observers and their evaluation of a seen watch, even though they are not aware of the fact that the shown time setting is inducing this effect. Practical implications of the observed findings and alternative explanations are discussed.